2013
DOI: 10.1371/journal.pone.0055491
|View full text |Cite
|
Sign up to set email alerts
|

“How Much Will I Get Charged for This?” Patient Charges for Top Ten Diagnoses in the Emergency Department

Abstract: ObjectivesWe examined the charges, their variability, and respective payer group for diagnosis and treatment of the ten most common outpatient conditions presenting to the Emergency department (ED).MethodsWe conducted a cross-sectional study of the 2006–2008 Medical Expenditure Panel Survey. Analysis was limited to outpatient visits with non-elderly, adult (years 18–64) patients with a single discharge diagnosis.ResultsWe studied 8,303 ED encounters, representing 76.6 million visits. Median charges ranged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 11 publications
0
57
0
Order By: Relevance
“…The Project SHARE intervention itself required signifi cant resources, primarily the "opportunity cost" of health educator and physician time; adding another patient to the intervention was calculated to require $110 in screening plus intervention costs. However, during the same period, the median charge for outpatient emergency department visits was $1,233 (Caldwell et al, 2013), suggesting that the estimated reduction in emergency department visits alone might cover screening and intervention costs. Although a full analysis of cost-effectiveness is outside the scope of the current study, reductions in health care utilization re- Notes: n = 1,073 for 6-month outcomes and n = 1,049 for 12-month outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…The Project SHARE intervention itself required signifi cant resources, primarily the "opportunity cost" of health educator and physician time; adding another patient to the intervention was calculated to require $110 in screening plus intervention costs. However, during the same period, the median charge for outpatient emergency department visits was $1,233 (Caldwell et al, 2013), suggesting that the estimated reduction in emergency department visits alone might cover screening and intervention costs. Although a full analysis of cost-effectiveness is outside the scope of the current study, reductions in health care utilization re- Notes: n = 1,073 for 6-month outcomes and n = 1,049 for 12-month outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…The strain on the health care system in the form of medical and productivity expenses adds to the indirect cost of ankle sprains. Caldwell et al [2], identified ''sprains and strains'' as the most common outpatient condition in the United States with 4.4 million emergency department visits per year. Nearly half of all ankle sprains occur during athletic activity (49.3 %) [3].…”
Section: Introductionmentioning
confidence: 99%
“…First, because of the interplay of government regulators, insurance companies, and several (often conflicting laws) the prices are completely non-transparent. 8 For example, a hospital might have a listed charge for a service (say, inserting an artificial knee) of $35 000, but the various insurance companies will actually pay $4000, and the copays from individual patients will vary from $100 to $31 000. 8,9 Moreover, there will be additional fees from the anesthesiologist (with the same range of costs and payments), for operating room time, etc.…”
mentioning
confidence: 99%
“…8 For example, a hospital might have a listed charge for a service (say, inserting an artificial knee) of $35 000, but the various insurance companies will actually pay $4000, and the copays from individual patients will vary from $100 to $31 000. 8,9 Moreover, there will be additional fees from the anesthesiologist (with the same range of costs and payments), for operating room time, etc. In fact, most hospital bills are incomprehensible even to experts, and many are often flat out wrong.…”
mentioning
confidence: 99%
See 1 more Smart Citation